Image and graphics technologies and applications : 13th Conference on Image and Graphics Technologies and Applications, IGTA 2018, Beijing, China, April 8-10, 2018, Revised selected papers /: 13th Conference on Image and Graphics Technologies and Applications, IGTA 2018, Beijing, China, April 8-10, 2018, Revised selected papers. (2018) - Unknown
No abstract available